Vector and reservoir control for preventing leishmaniasis (Review) (2015)
ABSTRACT: BackgroundLeishmaniasis is caused by the Leishmania parasite, and transmitted by infected phlebotomine sandflies. Of the two distinct clinicalsyndromes, cutaneous leishmaniasis (CL) aMects the skin and mucous membranes, and visceral leishmaniasis (VL) aMects internal organs.Approaches to prevent transmission include vector control by reducing human contact with infected sandflies, and reservoir control, byreducing the number of infected animals.ObjectivesTo assess the eMects of vector and reservoir control interventions for cutaneous and for visceral leishmaniasis.Search methodsWe searched the following databases to 13 January 2015: Cochrane Infectious Diseases Group Specialized Register, CENTRAL, MEDLINE,EMBASE, LILACS and WHOLIS, Web of Science, and RePORTER. We also searched trials registers for ongoing trials.Selection criteriaRandomized controlled trials (RCTs) evaluating the eMects of vector and reservoir control interventions in leishmaniasis-endemic regions.Data collection and analysisTwo reviewauthors independently searched fortrials and extracted data from includedRCTs.We resolved any disagreements by discussionwith a third review author. We assessed the quality of the evidence using the GRADE approachMain resultsWe included 14 RCTs that evaluated a range of interventions across diMerent settings. The study methods were generally poorly described,and consequently all included trials were judged to be at high or unclear risk of selection and reporting bias. Only seven trials reportedclinical outcome data which limits our ability to make broad generalizations to diMerent epidemiological settings and cultures.